Production of lactic acid and fructose from media with cane sugar using mutant of Lactobacillus delbrueckii NCIM 2365 - Patil, S. S.; Kadam, S. R.; Patil, S. S.; Bastawade, Kulbhushan B.; Khire, Jayant Malhar; Gokhale, D. V. (Letters in Applied Microbiology, 2006)
Aims: To examine the potential of Lactobacillus delbrueckii mutant, Uc-3 to produce lactic acid and fructose from sucrose-based media. Methods and Results: The mutant of L. delbrueckii NCIM 2365 was cultivated in shake flask containing hydrolysed cane sugar (sucrose)-based medium. The lactic acid yield and volumetric productivity with hydrolysed cane concentration up to 200 g l(-1) were in the range of 92-97% of the theoretical value and between 2.7 and 3.8 g l(-1) h(-1), respectively. The fructose fraction of the syrup produced was more than 95% when the total initial sugar concentration in the medium was higher (150-200 g l(-1)). There are no unwanted byproducts detected in the fermentation broth. Conclusions: We demonstrated that L. delbrueckii mutant Uc-3 was able to utilize glucose preferentially to produce lactic acid and fructose from hydrolysed cane sugar in batch fermentation process. Significance and Impact of the Study: These findings will be useful in the production of lactic acid and high fructose syrups using media with high concentrations of sucrose-based raw materials. This approach can lead to modification of the traditional fermentation processes to obtain value-added byproducts, attaining better process economics.
Keywords: fructose accumulation; hydrolyzed cane sugar; lactic acid production; Lactobacillus delbrueckii; Mutant

Purification, characterization and substrate specificity of thermostable alpha-galactosidase from Bacillus stearothermophilus (NCIM-5146) - Gote, M. M.; Khan, Mohammad Islam; Gokhale, D. V.; Bastawade, Kulbhushan B.; Khire, Jayant Malhar (Process Biochemistry, 2006)
An extracellular thermostable alpha-galactosidase from Bacillus stearothermophilus (NCIM-5146) has been purified to homogeneity by chromatographic step, using Phenyl Sepharose CL-4B column. The specific activity of the enzyme was increased approximately 389-fold, from 1.03 U/mg protein to 400 U/mg protein. The molecular mass of the purified enzyme as determined by SDS-PAGE and gel filtration was 79.9 and 165.9 kDa, respectively, suggesting dimeric nature. The purified alpha-galactosidase is a non-glycosylated protein with a pI of 4.9. The pH and temperature optima for the purified enzyme are 6.5-7.0 and 65 degrees C, respectively. The alpha-galactosidase is stable over a broad pH range (3-9) and its half-life of inactivation (t(1/2)) at 70 degrees C is 30 min. The partial N-terminal sequence of alpha-galactosidase showed remarkable homology (80% similarity) with earlier reported alpha-galactosidase from B. stearothermophilus NUB 3621. The secondary structure of the enzyme determined by circular dichroism (CD) spectroscopy exhibited alpha/beta class of protein and showed temperature induced conformational forms below and above the transition temperature. The purified enzyme showed biphasic Arrhenius plot with break point at 55 degrees C for pNPG and 50 degrees C for melibiose, raffinose and stachyose. The enzyme hydrolyzes alpha-1-3, alpha-1-4, and alpha-1-6 galactosidic linkages and not the beta-galactosidic linkages. Synthetic substrates pNPG and oNPG had lower K-m and higher K-cat as compare to natural substrates, melibiose, raffinose, and stachyose. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: alpha-galactosidase; Bacillus stearothermophilus (NCIM-5146); Purification; Secondary structure; thermostable enzyme

Purification and characterization of acidic lipase from aspergillus niger NCIM 1207 - Mhetras, Nutan; Bastawade, Kulbhushan B.; Gokhale, D. V. (Bioresource Technology, 2009)
An extracellular lipase from Aspergillus niger NCIM 1207 has been purified to homogeneity using ammonium sulfate precipitation followed by phenyl sepharose and Sephacryl-100 gel chromatography. This protocol resulted in 149 fold purification with 54% final recovery. The purified enzyme showed a prominent single band on SDS-PAGE. The purified enzyme is a monomeric protein of 32.2 kDa molecular weight and exhibits optimal activity at 50 degrees C. One interesting feature of this enzyme is its highly acidic pH optimum. The isoelectric point (pl) of lipase was 8.5. The purified lipase appears to be unique since it cleaved triolein at only 3-position releasing 1,2-diolein. Chemical modification studies revealed that His, Ser, Carboxylate and Trp are involved in catalysis. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Acidic lipase; Aspergillus niger; Positional specificity

Polylactic acid: synthesis and biomedical applications - Singhvi, M. S.; Zinjarde, S. S.; Gokhale, D. V. (Journal of Applied Microbiology, 2019)
Social and economic development has driven considerable scientific and engineering efforts on the discovery, development and utilization of polymers. Polylactic acid (PLA) is one of the most promising biopolymers as it can be produced from nontoxic renewable feedstock. PLA has emerged as an important polymeric material for biomedical applications on account of its properties such as biocompatibility, biodegradability, mechanical strength and process ability. Lactic acid (LA) can be obtained by fermentation of sugars derived from renewable resources such as corn and sugarcane. PLA is thus an eco-friendly nontoxic polymer with features that permit use in the human body. Although PLA has a wide spectrum of applications, there are certain limitations such as slow degradation rate, hydrophobicity and low impact toughness associated with its use. Blending PLA with other polymers offers convenient options to improve associated properties or to generate novel PLA polymers/blends for target applications. A variety of PLA blends have been explored for various biomedical applications such as drug delivery, implants, sutures and tissue engineering. PLA and their copolymers are becoming widely used in tissue engineering for function restoration of impaired tissues due to their excellent biocompatibility and mechanical properties. The relationship between PLA material properties, manufacturing processes and development of products with desirable characteristics is described in this article. LA production, PLA synthesis and their applications in the biomedical field are also discussed.
Keywords: Biocompatible; biodegradable; drug delivery; implants; l- and d-lactic acid; polylactic acid